Staging LaParoscopy to Assess Lymph NOde InvoLvement in Advanced GAstric Cancer (POLA)-Study protocol for a single-arm prospective observational multicenter study. - Karol Rawicz-Pruszyński; Katarzyna Sędłak; Zuzanna Pelc; Radosław Mlak; Jakub Litwiński; Paweł Mańko; Krzysztof Zinkiewicz; Iwona Paśnik; Katarzyna Cięszczyk; Timothy Pawlik; Bruno Märkl; Maria Erodotou; et al. (PLoS ONE, 2023)
Introduction In the era of neoadjuvant chemotherapy in advanced gastric cancer (GC), the role of staging laparoscopy (SL) will become more established. However, despite guidelines recommendations, SL for optimal preoperative staging remains underutilized. Diagnostic value of near-infrared (NIR) / indocyanine green (ICG) guided sentinel node (SN) mapping in GC confirmed its technical feasibility, however no data exist regarding its potential role in pathological nodal staging. To the best of our knowledge, current study is the first to evaluate the role of ICG in nodal staging of advanced GC patients undergoing SL. Materials and methods This single-arm prospective observational multicenter study was approved by the Bioethical Committee of Medical University of Lublin (Ethic Code: KE-0254/331/2018). The protocol is registered at clinicaltrial.gov (NCT05720598), and the study results will be reported according to the Strengthening of Reporting of Observational Studies in Epidemiology (STROBE) statement. The primary endpoint of this study is the identification rate of ICG-guided SN in advanced GC patients. The secondary endpoints include pathological and molecular assessment of retrieved SNs and other pretreatment clinical variables potentially associated with SL: pattern of perigastric ICG distribution according to patients' pathological and clinical characteristics, neoadjuvant chemotherapy compliance, 30-day morbidity, and mortality. Conclusion POLA study is the first to investigate the clinical value of ICG-enhanced sentinel node biopsy during staging laparoscopy in advanced GC patients in a Western cohort. Identifying pN status before multimodal treatment will improve GC staging process.